Macroeconomic and Environmental Determinants of FDI in 6-ASEAN Countries: A Panel Analysis - Muhammad Fathur Reza; Silvia Maura Madrim; Indanazulfa Qurrota A'yun (JAMPE (Journal of Asset Management and Public Economy), 2026)
Foreign Direct Investment (FDI) plays an important role in promoting economic growth, technology transfer, employment creation, and regional economic integration in developing countries, particularly in ASEAN economies. However, despite the growing literature on FDI determinants, previous studies have generally examined macroeconomic, environmental, financial, and technological factors separately, resulting in limited understanding of their combined effects on FDI inflows, especially in the ASEAN context. This study offers a more integrated perspective by simultaneously incorporating economic growth, carbon emissions, domestic credit, technology, and energy consumption into a unified empirical framework using the Seemingly Unrelated Regression–Panel Corrected Standard Errors (SUR-PCSE) approach. The study analyzes panel data from six ASEAN countries: Cambodia, Indonesia, Malaysia, the Philippines, Thailand, and Vietnam. The results indicate that economic growth, domestic credit, and energy consumption have significant positive effects on FDI inflows, while carbon emissions negatively affect FDI. In contrast, technology does not have a statistically significant effect on FDI in the observed countries. These findings suggest that ASEAN economies still rely heavily on macroeconomic stability, financial development, and infrastructure readiness in attracting foreign investment, while environmental sustainability is becoming increasingly important in shaping investment decisions. This study contributes to the literature by providing a more comprehensive framework for analyzing FDI determinants in ASEAN countries and offers policy insights for strengthening sustainable investment competitiveness in developing economies.